Comparative Assessment of the Bioremedial Potentials of Potato Resistant Starch-Based Microencapsulated and Non-encapsulated Lactobacillus plantarum to Alleviate the Effects of Chronic Lead Toxicity - Muhammad, Zafarullah; Ramzan, Rabia; Zhang, Shanshan; Hu, Haijuan; Hameed, Ahsan; Bakry, Amr M.; Dong, Yongzhen; Wang, Lufeng; Pan, Siyi (Frontiers in Microbiology, 2018)
Lead (Pb) is a well-recognized and potent heavy metal with non-biodegradable nature and can induce the oxidative stress, degenerative damages in tissues and neural disorders. Certain lactic acid bacterial strains retain the potential to mitigate the lethal effects of lead (Pb). . The present work was carried out to assess the lead bio-sorption and tolerance capabilities of Lactobacillus plantarum spp. Furthermore, potato resistant starch (PRS) based microencapsulated and non-encapsulated L. plantarum KLDS 1.0344 was utilized for bioremediation against induced chronic Pb toxicity in mice. The experimental mice were divided into two main groups (lead exposed and non-lead exposed) and, each group was subsequently divided into three sub groups. The lead exposed group was exposed to 100mg/L Pb(NO3)2 via drinking water and non-lead exposed group was supplied with plain drinking water during 7 weeks prolonged in vivo study. The accumulation of lead in blood, feces, renal and hepatic tissues and its pathological damages were analyzed. The effect of lead toxicity on the antioxidant enzyme capabilities in blood, serum, as well as, on levels of essential elements in tissues was also calculated. Moreover, KLDS 1.0344 displayed remarkable Pb binding capacity 72.34% and Pb tolerance (680mg/L). Oral administration of both non- and PRS- encapsulated KLDS 1.0344 significantly provided protection against induced chronic lead toxicity by increasing fecal Pb levels (445.65±22.28ug/g) and decreasing Pb in the blood up to 137.63±2.43ug/L respectively. KLDS 1.0344 microencapsulated with PRS also relieved the renal and hepatic pathological damages, and improved the antioxidant index by inhibiting changes in concentrations of glutathione peroxidase, glutathione, superoxide dismutase, malondialdehyde and activated oxygen species which were affected by the lead exposure . Overall, our results suggested that L. plantarum KLDS 1.0344 either in free or encapsulated forms hold the potentiality to deliver a dietetic stratagem against lead lethality.